1988
DOI: 10.1007/bf01639742
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-encapsulated ampicillin against Listeria monocytogenes in vivo and in vitro

Abstract: In an experimental infection caused by Listeria monocytogenes in mice a considerable enhancement (90-fold) of the therapeutic activity of ampicillin resulting from liposomal encapsulation was observed. The mechanism by which liposomes improved the therapeutic index of ampicillin in this infection appeared to be an increased delivery of the antibiotic to the site of infection, i.e. the liver and spleen. Substantial amounts of liposomal ampicillin were recovered from isolated Kupffer cells, the target cells of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Orozco et al (15) also found that empty liposomes increased the number of bacteria in organs of mice infected with M. tuberculosis. Bakker-Woudenberg et al (2) found that Listeria infections in mice were worse after treatment with placebo liposomes at high lipid doses but not at low lipid doses. Since distribution to nonhepatic reticuloendothelial system tissues (such as the spleen, bone marrow, and lung) and sustained levels in serum would appear to be desirable in the treatment of MAC, it may be necessary to carefully balance the advantages and potential disadvantages of high lipid doses to achieve the optimum therapy of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Orozco et al (15) also found that empty liposomes increased the number of bacteria in organs of mice infected with M. tuberculosis. Bakker-Woudenberg et al (2) found that Listeria infections in mice were worse after treatment with placebo liposomes at high lipid doses but not at low lipid doses. Since distribution to nonhepatic reticuloendothelial system tissues (such as the spleen, bone marrow, and lung) and sustained levels in serum would appear to be desirable in the treatment of MAC, it may be necessary to carefully balance the advantages and potential disadvantages of high lipid doses to achieve the optimum therapy of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, Majumdar et al [25] found that buffer-loaded liposomes inhibited Mycobac terium growth inside macrophages. On the other hand, several authors have found that intracellular bacterial infection, like Myco bacterium and Listeria, in mice was worse after treatment with placebo liposomes at a high lipid dose, but not a low lipid dose [12,26,27]. In this context, it has been described that with small doses, most intact liposomes are retained by the liver (with larger doses, the ability of the liver to clear particles from the circulation may be overwhelmed), and that the amount remaining in the circulation that can be taken up by the spleen and bone mar row thus increases [28].…”
Section: Discussionmentioning
confidence: 99%
“…Be sides, encapsulation markedly alters their pharmacokinetics, e.g., shifts drug accumula tion from the kidney to other organs, thus potentially reducing the toxicity of the free drug [10,11], In fact, liposomes arc success fully used as carriers of aminoglycosides in experimental models of bacterial infections, such as those caused by Listeria monocyto genes, Mycobacterium spp., Salmonella spp., Klebsiella pneumoniae, and Brucella spp. [9,10,[12][13][14][15],…”
Section: Introductionmentioning
confidence: 99%
“…Higher intracellular concentrations of antibiotics enhance the antibacterial activity of phagocytic cells against to intracellular infections when compared to the same free drug dose (Emmen and Storm, 1987;Bas et al, 2000). It was reported that LA and ampicillin- Bakker-Woudenberg et al, 1986;Carryn et al, 2003) or experimental salmonellosis (Fattal et al, 1989), listeriosis (Bakker-Woudenberg et al, 1985, 1988Fattal et al, 1991). On the contrary, it was reported that FA had no good bactericidal activity, nor need higher concentrations to the treatment in the intracellular infections caused by non-typeable Haemophilus influenzae (Ahren et al, 2002), non-typhoid Salmonella (Chiu et al, 1999) or experimental salmonellosis (Fattal et al, 1989).…”
Section: Resultsmentioning
confidence: 99%